2018
DOI: 10.1109/tdei.2018.006670
|View full text |Cite
|
Sign up to set email alerts
|

The different stages of PRPD pattern for positive point to plane corona driven by a DC voltage containing ripple

Abstract: The different phase resolved partial discharge patterns, which can be recognized when a positive dc voltage containing a ripple due to a half-wave rectification is used are presented in this paper. Results are given from corona onset to the appearance of breakdown streamers. The outcomes are five different patterns, which represent the four stages of positive corona and their transition zones. Three of them are clearly identifiable with respect to patterns from other discharge sources that have already been re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Just like the AC PRPD method provides a phase reference, DC PRPD diagnostics feature a phase reference by a superimposed AC ripple. It was introduced by Dezenzo et al [9] for basic high voltage arrangements and enables the creation of PRPD patterns related to different failure types. The PRPD patterns in chapter IV are measured using an Omicron MPD 800, a one-way rectification, and a test adapter with a conductive elastomer as a contact electrode.…”
Section: A DC Prpd Diagnosticsmentioning
confidence: 99%
“…Just like the AC PRPD method provides a phase reference, DC PRPD diagnostics feature a phase reference by a superimposed AC ripple. It was introduced by Dezenzo et al [9] for basic high voltage arrangements and enables the creation of PRPD patterns related to different failure types. The PRPD patterns in chapter IV are measured using an Omicron MPD 800, a one-way rectification, and a test adapter with a conductive elastomer as a contact electrode.…”
Section: A DC Prpd Diagnosticsmentioning
confidence: 99%
“…Investigating the discharge physics under DC voltage stress requires a DC voltage with low ripple. This is necessary, because a ripple factor δU of a few percent can lead to a phase-dependent concentration of PD impulses in the voltage maximum and would therefore influence the PD behaviour significantly [35]. For this reason, a symmetric Greinacher voltage doubler circuit (Figure 3) is used to generate high DC voltages [4].…”
Section: Generation Of High DC Voltage With Low Ripplementioning
confidence: 99%
“…These ripples are periodic and thus helps to overcome the shortcoming of using PRPD analysis for DC voltage stress. Dezenzo et al [5,22] have carried out PRPD analysis of positive and negative ripple on needle plane configuration and reported that at high voltage, discharge magnitude follows inverse of the voltage curve due to the presence of dominant space charge. Fig.…”
Section: Phase-resolved Partial Discharge Analysismentioning
confidence: 99%
“…The process of AC/DC conversion introduces distortion in output voltage waveform which reduces the voltage withstand capability due to the formation of harmonic voltage with different total harmonic distortions (THD) leading to high dv/dt stress. In an OIP specimen, pulsed DC have been reported to have a significant influence on partial discharge (PD) characteristics [5]. This necessitates the need to test the OIP material under possible cases of voltage waveform distortion.…”
Section: Introductionmentioning
confidence: 99%